Pre-earthquake kidney function is a predictor of outcomes in earthquake-related crush syndrome - Danis, Ramazan; Ozturk, Savas; Kocyigit, Ismail; Kilic, Jehat; Civan, Merve; Sahutoglu, Tuncay; Tuglular, Serhan (Bmc, 2025)
Background The devastating earthquakes in Kahramanmara & scedil;, T & uuml;rkiye, in February 2024, caused extensive trauma and loss of lives, causing unique challenges in the management of earthquake-related crush syndrome. The current study investigates the prognostic value of pre-earthquake kidney function for mortality prediction in patients diagnosed with crush syndrome. Methods A multi-center retrospective analysis was performed using data from 469 patients treated at 46 nephrology clinics. Pre-earthquake Kidney function, defined by serum creatinine and estimated glomerular filtration rate (eGFR) levels, was obtained from pre-earthquake health records. Clinical findings, laboratory parameters, complications, and survival probabilities were analyzed. Multivariate Cox regression was used to identify independent predictors of in-hospital mortality. Results The mean age of participants was 42.56 +/- 16.92 years (Non-survivors: 50.46 +/- 20.03 years, Survivors: 42.34 +/- 16.80 years (p = 0.172)). The in-hospital mortality rate was 2.8%. Non-survivors exhibited significantly higher pre-earthquake creatinine levels than survivors (1.04 +/- 0.61 mg/dL vs. 0.77 +/- 0.33 mg/dL, p = 0.03), with lower eGFR (85.2 +/- 34.7 mL/min/1.73 m(2 )vs. 115.8 +/- 39.4 mL/min/1.73 m(2 ), p = 0.008). Compared with survivors, non-survivors had higher incidences of AKI (92.3% vs. 61.6%, p = 0.037) and more severe metabolic disturbances, including hyperkalemia (5.41 +/- 1.72 mmol/L vs. 5.13 +/- 0.98 mmol/L, p = 0.008). Regression analysis revealed that pre-earthquake creatinine (HR: 9.121, 95% CI: 2.686-30.970, p < 0.001) and potassium levels at admission (HR: 3.338, 95% CI: 1.540-7.232, p = 0.002) were independent predictors of mortality. Conclusions Pre-earthquake kidney function significantly predicts mortality in crush syndrome patients, highlighting the importance of baseline kidney assessment in disaster preparedness.
Keywords: Crush syndrome; kidney function; mortality; disaster nephrology; acute kidney injury; hyperkalemia; T & uuml;rkiye